Thermal performance of the Urban Weather Generator model as a tool for planning sustainable urban development - Alchapar, Noelia Liliana; Pezzuto, Cláudia Cotrim; Correa, Erica Norma; Salvati, Agnese (Geographica Pannonica, 2019)
The research aims at assessing the sensitivity of the Urban Weather Generator v4.1 to the application of different mitigation strategies for the urban heat island under two climatic contexts: desert climate (Mendoza city) and tropical climate (Campinas city). Twenty-four scenarios that modify their morphologic and material parameters were simulated. The results showed that the temperature of the air predicted by the UWG model is not significantly sensitive to the changes produced by the application of different strategies in urban contexts of equal H/W aspect; however, it does show sensitivity to the variation of the H/W aspect (ΔTa ≤ 1.3°C) and the climate context. The highest performance of the UWG model was recorded on the surface temperatures of the urban envelope, with a maximum difference in surface temperature was recorded on high aspect ratio with high albedo in arid climate, (Ts of roof=28°C).
Keywords: Thermal performance; strategies; H/W; high albedo; Urban Weather; city